Equity incentive schemes, investor protection and corporate performance: evidence from China - Su, Zili; Alexiou, Constantinos (Emerald, 2019)
Purpose On the basis of corporate governance and agency cost theory, using the fifth sub-indicator of Fan et al. China Marketization Index as the regional investor protection index (IPI), the purpose of this paper is to explore the impact of equity incentives and regional investor protection on corporate payout policies and corporate performance. Design/methodology/approach This paper establishes ordinary least squares regression model to examine interactions between the effects of equity incentives and regional investor protection upon firms’ dividend payouts. In addition, the authors also explore whether the joint effects on payouts are altered in the presence of growth opportunities, and investigate the effects of interactions between equity incentives and regional investor protection on corporate performance. Findings The authors observe that firm managers appear to abuse equity incentives by increasing dividend payouts. However, regional investor protection can potentially restrain such behavior. The restraining effect depends on the firms’ growth opportunities, on the basis of which the effect on cash (stock) dividends is found to be weaker (stronger) in high-growth firms – and stronger (weaker) in low-growth firms. Further evidence indicates that the restraining effect of regional investor protection on selfish dividend-related behavior encouraged by equity incentives may also prove valuable in encouraging exploitation of these incentives so as to enhance corporate performance. Practical implications Since reforming investor protection laws and improving judicial quality are difficult and lengthy at a country level. Improving regional levels of investor protection, however, seems more feasible and effective. Through measures encouraging the development of intermediaries, increases in the number of lawyers – all of which seem likely to constrain behavior harmful to the interests of investors – the provincial administrations can reasonably expect to contribute toward improvements in the performance of firms and the development of the economy in their region. This paper provides encouragement to regional policy makers in China and in other developing countries. Originality/value This paper uses a regional index of investor protection to study the impact on corporate dividends and performance, in contrast with most previous studies, which have examined these issues at country or individual firm levels. The use of a regional-level investor IPI in this paper therefore fills a gap by coming in between the country- and firm-level indicators typically used in previous research, thus providing a new perspective on investor protection issues
Keywords: Corporate performance; investor protection; equity incentive; payouts; G14; G18